Seminarji iz medicinske etike - Zwitter, Matjaž (University of Maribor Press, 2025)
Seminars in Medical Ethics. At the Medical Faculty of the University of Maribor, students of the 4th year of general medicine, as well as students of the first year of dental medicine, have to pass a curriculum in medical ethics. An essential part of teaching emdical ethics are seminars with active student participation. Seminars, as presented in this volume, cover a wide range of topics: discussions about recent real cases of malpractice or conflicts in health care, theoretical issues, and presentations of medical profession in a literary form such as novels and drama.